Paronychia - Vandervall, OMS III, Korinn; Yehl, DO, Mary Ann; Tjiattas-Saleski, DO, MBA, FACOEP, Lindsay (Osteopathic Family Physician, 2018)
A 73-year-old female with past a medical history of diabetes mellitus type II, hypertension and thyroid disease presented to the Urgent Care Center with right distal thumb pain and swelling (Figure 1). She had been seen two days prior, diagnosed with paronychia and prescribed cephalexin 500mg three times daily. She reported no improvement in the antibiotics and warm soaks. She did not report any associated fevers or chills. On her second visit, incision and drainage were performed. She discontinued cephalexin, and trimethoprim/sulfamethoxazole was started.